Infantile acropustulosis: a case report - Devaraj, Yogesh; Sathyanarayana, Belagola Dasegowda; Swaroop, Mukunda Ranga; S., Suman; Bidarkar, Shruti; Sreekanth S., Sindhujaa (International Journal of Research in Dermatology, 2018)
Acropustulosis is a benign cutaneous disease. It is characterized by recurrent crops of pruriginous vesicles, papules and pustules affecting the acral areas. It is self-resolving. Its etiology is unknown but it can be associated with scabies. Typically begins between 2 to 24 months of life, but can also occur in children. We report a case of infantile acropustulosis in a 11-year-old boy which started at the age of 3 years.